Modern Psychological Technologies for Correcting Conflict Situations in Limited Coalitions (Based on Volleyball Material) - Doroshenko, E. Yu.; Shevyakov, O.; Melnyk, M.; Oliinyk, M. O.; Oliinyk, I.; Vaniuk, D. V.; Дорошенко, Едуард Юрійович; Шевяков, О.; Мельник, М.; Олійник, Михайло Олександрович; Олійник, І.; Ванюк, Дар'я Валеріївна (My University, 2023)
The purpose of the work – to determine the peculiarities of the response of sportswomen to conflict situations in the conditions of a limited coalition of the volleyball team in order to optimize the process of sports training. Materials and methods. Participants: 30 amateur volleyball players (women), who participated in park and beach volleyball competitions in the 2022-2023 season under the auspices of the Zaporizhzhia Regional Volleyball Federation. Age range: 18-27. Methods: Analysis and systematization of data from scientific and methodical literature and the electronic resource of global information network “Internet”; pedagogical observations; psychological testing according to the method of K. Thomas “Determining the style of behavior in a conflict situation”; pedagogical experiment of controlling orientation; methods of mathematical statistics. Results. The analysis of the experimental indicators allows us to state that the volleyball players of the main group significantly improved the “cooperation” (+6.67%) and “compromise” (+6.67%) indicators, while the “avoidance” indicator significantly decreased (-13.33%). Based on this, we note that the technology for correcting conflict situations in limited coalitions of the volleyball team is quite effective (indicators of volleyball players of the main group). Among the volleyball players of the control group, an increase in indicators according to the “compromise” criteria (+6.67%) and a decrease according to the “avoidance” criterion (-6.66%) were recorded. Conclusion. Modern technologies of psychological training in volleyball, which relate to issues of correction of conflict situations in limited coalitions, are a prerequisite for increasing the effectiveness of the competitive activity of volleyball players. The main ways of applying these technologies in the training process in volleyball are the psychological diagnosis of female athletes taking in to account their personal qualifications, social roles in the limited coalition of the volleyball team; targeted application in competitive micro- or mesocycles of training to increase the effectiveness of training and competitive activities in limited coalitions. Мета роботи – визначити особливості реагування спортсменок на конфліктні ситуації в умовах обмеженої згуртованості волейбольної команди з метою оптимізації процесу спортивної підготовки. Матеріал і методи. Учасники: 30 волейболістів-любителів (жінок), які брали участь у змаганнях з паркового та пляжного волейболу сезону 2022-2023 під егідою Запорізької обласної федерації волейболу. Віковий діапазон: 18-27. Методи. Аналіз та систематизація даних науково-методичної літератури та електронного ресурсу глобальної інформаційної мережі «Інтернет»; педагогічні спостереження; психологічне тестування за методикою К. Томаса «Визначення стилю поведінки в конфліктній ситуації»; педагогічний експеримент контролюючої спрямованості; методи математичної статистики. Результати. Аналіз експериментальних показників дозволяє стверджувати, що у волейболісток основної групи суттєво покращилися показники «співпраця» (+6,67%) та «компроміс» (+6,67%), а показник «уникнення» значно знизився (- 13,33%). Виходячи з цього, зазначимо, що технологія корекції конфліктних ситуацій в обмежених складах волейбольної команди є досить ефективною (показники волейболістів основної групи). Серед волейболісток контрольної групи зафіксовано зростання показників за критерієм «компроміс» (+6,67%) та зниження за критерієм «уникнення» (-6,66%). Висновок. Сучасні технології психологічної підготовки у волейболі, які стосуються питань корекції конфліктних ситуацій в обмежених коаліціях, є передумовою підвищення ефективності змагальної діяльності волейболістів. Основними напрямами застосування цих технологій у навчально-тренувальному процесі у волейболі є психологічна діагностика спортсменок з урахуванням їх особистісних якостей, соціальних ролей у обмеженому складі волейбольної команди; цілеспрямоване застосування в змагальних мікро- або мезоциклах підготовки для підвищення ефективності тренувальної та змагальної діяльності в обмежених коаліціях.
Сучасні психологічні технології корекції конфліктних ситуацій в обмежених коаліціях (на матеріалі волейболу)
Doroshenko E. Yu. - https://orcid.org/0000-0001-7624-531X; Oliinyk M. O. - https://orcid.org/0000-0003-4131-7664; Vaniuk D. V. - https://orcid.org/0000-0002-6069-074X.
Keywords: volleyball; training; psychological technologies; correction; limited coalition; волейбол; навчання; психологічні технології; корекція; обмежена коаліція